KNOWLEDGE SPILLOVERS, INNOVATION ACTIVITIES, AND COMPETITIVENESS OF INDUSTRIES IN EU MEMBER AND CANDIDATE COUNTRIES - Hashi, Iraj; Stojčić, Nebojša (Economic Annals, 2013)
The impact of innovation activities on the performance and competitiveness of firms, industries, and nations has been a matter of considerable interest over the past few decades. The existing empirical work has widened our knowledge of the complexity of the innovation process and its impact on the ability of firms to compete. This study investigates how knowledge spillovers generated through firms’ innovation activities affect the ability of their industries to compete in terms of quality. The data from the Community Innovation Survey 2006 for several EU member and candidate countries that have recently become available are combined with other EU-wide datasets to create an industry database containing information on innovation activities and performance at industry level. A simultaneous equations framework is used to examine the interdependencies between knowledge spillovers, innovation activities, quality upgrading, and the market share of industries from the selected countries in the single European market. The results of the investigation provide support for the relationship between innovation, quality upgrading, and market share of industries, and point to several types of spillover which are relevant for the competitiveness of national industries in EU member states.